Evaluation of anti-tumor activity of ethanolic extract of Glycyrrhiza glabra against Ehrlich ascites carcinoma in swiss albino mice - K., Jayanthi M.; Madhunapantula, SubbaRao V.; Reddy, Divya K.; Mryuthunjaya, K.; N., Manjula S. (International Journal of Basic & Clinical Pharmacology, 2017)
Background: Cancer is one of the most life threatening diseases which is in need of newer drug development. The use of plant products with potent antioxidant and cytotoxic activity is upcoming Studies reveal that herbal product have increased efficacy as well as decreased side effects, with this in mind the present study was undertaken to assess the antitumor activity of extracts of Glycyrrhiza glabra (GG) against ehrlich ascites carcinoma in swiss albino mice. Methods: The extracts of roots of GG was collected and acute toxicity study was done following which the antitumor effect of extracts of GG was assessed by change in the body weight, mean survival time (MST), and percentage increased life span (% ILS). MST of each group containing six mice was monitored by recording the mortality daily for 6 weeks and % ILS was calculated. The hematological parameters and biochemical assays were also measured. Results: Extracts of GG showed a significant reduction in % increase in tumor induced body weight of the mice. The % increase in life span was also significant in the higher dose of GG (500 mg/kg). The combination of GG with standard drug cisplatin had better efficacy in terms of % ILS, hematological and biochemical parameters. The results obtained were statistically significant. Conclusions: The antitumor activity studies measuring the viability of cancer cells when exposed to the ethanolic extract of Glycyrrhiza glabra showed a potent cell-killing effect, indicating the presence of anti-cancer principles in the preparation.